Mucosal Immunoregulatory Properties of Tsukamurella inchonensis to Reverse Experimental Food Allergy - Smaldini, Paola L.; Trejo, Fernando M.; Rizzo, Gastón P.; Comerci, Diego J.; Kampinga, Jaap; Docena, Guillermo H. (Frontiers in Immunology, 2021)
The intestinal mucosa is lined by epithelial cells, which are key cells to sustain gut homeostasis. Food allergy is an immune-mediated adverse reaction to food, likely due to defective regulatory circuits. Tsukamurella inchonensis (Ti) is a non-pathogenic bacterium with immunomodulatory properties. We hypothesize that the anti-inflammatory effect of dead Ti on activated epithelial cells can modulate milk allergy through the restoration of tolerance in a mouse model. Epithelial cells (Caco-2 and enterocytes from mouse gut) and macrophages were stimulated with Ti and induction of luciferase under the NF-B promoter, ROS and cytokines were studied. Balb/c mice were mucosally sensitized with cow´s milk proteins plus cholera toxin and orally challenged with the allergen to evidence hypersensitivity symptoms. Thereafter, mice were orally administered with heat-killed Ti as treatment and then challenged with the allergen. The therapeutic efficacy was in vivo (clinical score and cutaneous test) and in vitro (serum specific antibodies and cytokines-ELISA, and cell analysis-flow cytometry) evaluated. Heat-killed Ti modulated the induction of pro-inflammatory chemokines, with an increase of anti-inflammatory cytokines by intestinal epithelial cells and by macrophages with decreased OX40L expression. In vivo, oral administration of Ti increased the frequency of lamina propria CD4+CD25+FoxP3+ T cells, and clinical signs were lower in Ti-treated mice compared with milk-sensitized animals. In vivo depletion of Tregs (anti-CD25) abrogated Ti immunomodulation. In conclusion, these bacteria modulate the NF-B pathway and the induction of OX40L to reverse experimental food allergy